2009
DOI: 10.1158/1078-0432.ccr-08-2686
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection Induces Genetic Instability of Nuclear and Mitochondrial DNA in Gastric Cells

Abstract: Purpose: Helicobacter pylori is a major cause of gastric carcinoma. To investigate a possible link between bacterial infection and genetic instability of the host genome, we examined the effect of H. pylori infection on known cellular repair pathways in vitro and in vivo. Moreover, various types of genetic instabilities in the nuclear and mitochondrial DNA (mtDNA) were examined. Experimental Design: We observed the effects of H. pylori infection on a gastric cell line (AGS), on C57BL/6 mice, and on individuals… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 35 publications
6
102
1
3
Order By: Relevance
“…Our observation of H. hepaticus-induced down-regulation of DNA repair transcripts is consistent with studies of H. pylori infection, which has been shown to suppress DNA repair gene expression in infected cells in culture and in infected mouse and human tissues (57,58). Whereas Machado et al observed that infection caused reduced expression of base excision and mismatch repair genes and concomitant increases in genomic instability (58), Kim et al demonstrated that H. pylori coculture with gastric cancer cells lines caused reduced levels of both mRNA and protein for both MutS and MutL mismatch repair protein, with heat-sensitive bacterial products responsible for the reductions (57).…”
Section: Colitis-associated Changes In Gene Expression Reflect Bacterialsupporting
confidence: 90%
“…Our observation of H. hepaticus-induced down-regulation of DNA repair transcripts is consistent with studies of H. pylori infection, which has been shown to suppress DNA repair gene expression in infected cells in culture and in infected mouse and human tissues (57,58). Whereas Machado et al observed that infection caused reduced expression of base excision and mismatch repair genes and concomitant increases in genomic instability (58), Kim et al demonstrated that H. pylori coculture with gastric cancer cells lines caused reduced levels of both mRNA and protein for both MutS and MutL mismatch repair protein, with heat-sensitive bacterial products responsible for the reductions (57).…”
Section: Colitis-associated Changes In Gene Expression Reflect Bacterialsupporting
confidence: 90%
“…H. pylori infection of cultured gastric epithelial cells down-regulates the components of the mismatch repair (MMR) and base excision repair machineries at the RNA and protein levels and impairs the efficiency of DNA repair as judged by MMR activity assay (13,14). The down-regulation of MMR proteins was confirmed in experimentally infected murine gastric mucosa (14) and can be reversed by Helicobacter eradication in patients (15), suggesting that impaired DNA repair also is a hallmark of H. pylori infection in vivo.…”
mentioning
confidence: 99%
“…In H. pylori-infected patients, mtDNA mutations are significantly more frequent in patients with gastric cancer than in cancer-free patients (23). According to our previous studies, mtDNA mutations are induced in vitro in H. pyloriinfected gastric epithelial cells and in the gastric mucosa of chronically infected mice (24,25). A decrease in mtDNA content has also been described in most tumor tissues of advanced gastric cancer, compared with nearby nontumor control tissue (26)(27)(28).…”
Section: Introductionmentioning
confidence: 85%